Doctors' reporting of mental health stigma and barriers to help-seeking. (17th September 2021) - Wijeratne, C; Johnco, C; Draper, B; Earl, J
Abstract: Background: Medical practitioners experience high levels of mental disorders but may be reluctant to seek care. Aims: To determine medical practitioner attitudes towards other doctors with anxiety/depression, barriers to seeking mental healthcare, treatments received for depression and the effects of age. Methods: Data from the National Mental Health Survey of Doctors and Medical Students, conducted in Australia, were analysed ( N = 10 038 medical practitioners). Attitudes to anxiety/depression were assessed with 12 statements (total stigma score, range 12–60). Barriers to seeking professional help, and coping strategies used, for anxiety/depression were measured. Practitioners with a history of depression were asked what personal supports and treatments were received. Practitioners were compared by age—younger (40 years and younger), middle-aged (41–60) and older (61+). Results: Attitudes and help-seeking behaviours varied with age. Older doctors had a more positive outlook and less total stigma, with the exception that they believed a doctor with anxiety/depression was less reliable. Younger practitioners were most likely to report barriers, such as confidentiality, impact on career progression and registration, to seeking help. For practitioners with depression, counselling and counselling plus medication were most likely to be received by the younger and middle-aged groups, whereas medication alone was most likely to be received by the middle-aged and older groups. Conclusions: Stigmatizing attitudes towards mental disorder and barriers to help-seeking remain prevalent within the medical profession. Our results suggest doctors' health programs should address mental health stigma in younger practitioners and facilitate education about psychological treatments in older practitioners.